Wage insurance for displaced workers - Benjamin Hyman; Brian K. Kovak; Adam Leive (Federal Reserve Bank of New York, 2024)
Wage insurance provides income support to displaced workers who find reemployment at a lower wage. We analyze wage insurance in the context of the U.S. Trade Adjustment Assistance (TAA) program by merging linked employer-employee Census data to TAA petitions and leveraging a discontinuity in eligibility based on worker age. Wage insurance eligibility increases short-run employment probabilities and leads to higher long-run cumulative earnings. We find shorter non-employment durations largely drive increased long-term earnings among workers eligible for wage insurance. Our results are quantitatively consistent with a standard non-stationary partial equilibrium search model. The program is self-financing even under conservative assumptions.
Keywords: J6; J65; J01; 330; social insurance; displaced workers; regression discontinuity